Karakter Fenotipik Tanaman Stroberi Festival (Fragaria x ananassa D.) Hasil Induksi Kolkisin Pada Konsentrasi 0,05% dan 0,01% - Riza Aristya, Ganies; Setiadi Daryono, Budi (Biogenesis, 2014)
Strawberries were a lot of holticulture commodities consumed by the people of Indonesia. Strawberry consumption continues to increase over time in Indonesia but not matched by production. This it because the strawberry is native to subtropical climate so that production in Indonesia limited in the plateau regional still affected by the tropical climate. Therefore, it is necessary to increase the production of both quality and quantity of strawberries, one with plant breeding through the induction of colchicine. The objective of this research were to determine the differences in phenotypic characters of strawberry plants with the control and induction results to determine the length of time and the induction colchicine 0,05% and 0,01% on the Festival cultivar of strawberry most effective. Research were done by inducing with 0,05% and 0,01% colchicine in leaves, roots 24 hours and 36 hour, the root and leaves of 24 and 36 hour. The observed for 6 months long leaf growth, leaf width,number of leaves, stem circumference, plant height, bloom vast flower and volumes of the fruit. The results indicate that the induction of the leaf growth at the optimal parameter leaf lenghth, leaf width and number of leaves. While 24-hour induction of root growth at optimum height and volume of fruitplants, then root induction at 36 hour to flowers bloom. Induction in root and leaves 36 hour optimum growth on trunck circumference. From this study it could be concluded that there are differences in the character of the strawberry crop cultivar Festival phenotype induction results colchicine 0,05% and 0,01% with control. Induction for 36 hours and induction on leaves was most effective for induction of strawberry cultivar Festival.Keywords: character phenotype, colchicine, festival